Music Therapy and Music-Based Interventions in Pediatric Neurorehabilitation - Elisa Milcent Fernandez; Christopher J. Newman (Children)
Background: Music therapy and music-based interventions are increasingly recognized as valuable adjuncts in pediatric neurorehabilitation, leveraging rhythm, singing, instrument playing, and improvisation to support children with neurological disabilities. Objective/Method: This narrative review synthesizes evidence from studies published between 2000 and 2025, focusing on children aged 3 to 18 years receiving neurorehabilitation. Results: The literature demonstrates that music therapy and music-based interventions can improve motor function—particularly gait and upper limb coordination—as well as speech production, while also reducing anxiety and enhancing participation. Techniques such as rhythmic auditory stimulation and melodic intonation therapy have shown promise in targeting movement and communication deficits. Music therapy is further associated with positive effects on vital signs and emotional well-being, supporting its role in holistic care. Neurobiological findings suggest that music-based interventions may promote neuroplasticity and strengthen brain connectivity, though high-quality mechanistic studies remain limited. Conclusions: Despite methodological heterogeneity and small sample sizes in the current literature, the overall evidence supports music therapy and music-based interventions as accessible, cost-effective, and child-centered complements to standard neurorehabilitation. Future research should prioritize rigorous clinical trials and neurobiological investigations to clarify mechanisms and optimize therapeutic protocols.